THE VERNACULAR HIATUS: MODERNITY, TRADITION, AND ETHNICITY - Alexander R. Cuthbert; Gusti Ayu Made Suartika (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2016)
The following paper began by serving as a general introduction to this special issue of Ruang – Space. In the course of writing it morphed into a slightly different offering. While a general overview remains, covering linguistic problems and interrelationships, the paper not only offers a basic thesis about Vernacular/Ethnic architecture – thatthe central purpose of vernacular architecture isto inform the present, not to define the past, it also suggeststhe proof. In the course of outlining this idea, works contributed to two former books are cited. The first, Home- A Portfolio of Home over the Ages generated a basic structure for the purpose of analysing the generic features of home. Work previously unpublished is included to reveal the logic and method behind the eight historical chapters in the book. The second Vernacular Transformations – Architecture, Place and Tradition, specifically chapter one, illustrates the development of the thesis in significant detail, and modifies the original model on critique. The article concludes by suggesting that the thesis has been adequately supported, and that the method derived from realist philosophy using necessary and contingent features is useful until someone can improve on this overall system. Keywords: vernacular; ethnic; necessary and contingent features; counter representation. Abstrak Tulisan ini pada awalnya didedikasikan sebagai prolog untuk edisi khusus Jurnal Ruang-Space yang mengambil tema permukiman etnik. Namun dalam proses penyusunannya, telah berubah menjadi artikel yang secara khusus membahas tentang aspek linguistik dan hubungan antar elemen penyusun arsitektur etnik. Artikel ini tidak hanya memaparkan pernyataan mendasar terkait arsitektur vernakular/etnik, tetapi juga menyajikan bukti-bukti pendukung. Sebuah thesis yang diusung disini ialah pemahaman terkait arsitektur vernakular dibutuhkan untuk menginformasikan kondisi-kondisi yang terjadi saat ini, dan bukan untuk mendefinisikan masa lampau. Dalam konteks ini, dua publikasi terdahulu telah dijadikan referensi. Pertama, Home - A Portfolio of Home over the Ages yang dibangun melalui analisa beragam fitur dasar penyusun sebuah 'home-rumah.' Bermacam wujud rumah, yang awalnya belum dipublikasikan, telah dirangkul untuk memahami logika dan metode yang melatarbelakangi penyusunan delapan bab dari buku ini. Kedua, Vernacular Transformations – Architecture, Place and Tradition, khususnya Bab pertama, yang memberikan ilustrasi secara detil, bagaimana arsitektur vernakular dipahami. Di akhir, artikel ini merangkum jika kemunculan thesis di atas telah didukung dengan metode yang dilandasi filosofi seorang realist, dengan memanfaatkan fitur-fitur yang ada. Ini hanya akan berubah jika pernyataan/ide baru muncul, dengan tujuan untuk memperbaiki thesis ini. Kata kunci: vernakular, etnik, rumah, tradisi